Survey of County-Level Heat Preparedness and Response to the 2011 Summer Heat in 30 U.S. States - White-Newsome, Jalonne L. (NLM-Export, 2014)
Background: Adapting to extreme heat is becoming more critical as our climate changes. Previous research reveals that very few communities in the United States have programs to sufficiently prevent health problems during hot weather. Objective: Our goal was to examine county-level local heat preparedness and response in 30 U.S. states following the unusually hot summer of 2011. Methods: Using a multimodal survey approach, we invited local health and emergency response departments from 586 counties to participate in the largest survey to date of heat preparedness and response in the United States. County-level responses were pooled into national and regional-level summaries. Logistic regressions modeled associations between heat planning/response and county characteristics, including population, poverty rates, typical summer weather, and 2011 summer weather. Results: Of 586 counties, 190 (32%) responded to the survey. Only 40% of these counties had existing heat plans. The most common heat responses were communication about heat, outreach, and collaborations with other organizations. Both heat preparedness and heat response were, on average, more extensive in counties with higher populations, lower poverty rates, and lower percentages of older people. Heat response was generally more extensive in counties with heat plans. Conclusions: Most responding counties were underprepared for extreme heat in 2011 and lacked a formal response plan. Because counties with heat plans were more likely to act to prevent adverse heat impacts to residents, local health departments should consider adopting such plans, especially because increased extreme heat is anticipated with further climate change. Citation: White-Newsome JL, Ekwurzel B, Baer-Schultz M, Ebi KL, O’Neill MS, Anderson GB. 2014. Survey of county-level heat preparedness and response to the 2011 summer heat in 30 U.S. States. Environ Health Perspect 122:573–579; http://dx.doi.org/10.1289/ehp.1306693